Pseudorabies Virus - Tang, Yan-Dong; Li, Xiangdong (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pseudorabies virus (PRV) is an important swine pathogen that impacts swine industry worldwide. PRV belongs to the alphaherpes virus subfamily of the herpesviruses that has been widely used as a model herpes virus. Most recently, PRV has been reported sporadically spillover into human and other animals. This book collects the newest advances in the field of pseudorabies virus research, including critical reviews and research on viral evolution, replication, virus-host interaction, pathogenesis and immunity, and novel antiviral strategies.